2020
DOI: 10.3390/en13154024
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Impact of Daylighting and the Corresponding Lighting Controls to the Users of Office Buildings

Abstract: Daylight utilization significantly contributes to energy savings in office buildings. However, daylight integration requires careful design so as to include variations in daylight availability and maintain a balance between factors such as lighting quality and heat gain or loss. Designers with proper planning can not only improve the visual environment and create higher-quality spaces, but simultaneously minimize energy costs for buildings. The utilization of photosensors can exploit the benefits of daylightin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 80 publications
0
19
0
Order By: Relevance
“…The recommended lighting standards should reflect the lighting conditions at which visual tasks can be conducted effectively and comfortably in an energyefficient way which complies with the mandate against light pollution. 13,17,[30][31][32][33][34] Within this context, our study evaluates whether current lighting standards address the needs both of pseudophakic and normophakic patients by exploring the impact of illuminance on visual acuity both theoretically and experimentally.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recommended lighting standards should reflect the lighting conditions at which visual tasks can be conducted effectively and comfortably in an energyefficient way which complies with the mandate against light pollution. 13,17,[30][31][32][33][34] Within this context, our study evaluates whether current lighting standards address the needs both of pseudophakic and normophakic patients by exploring the impact of illuminance on visual acuity both theoretically and experimentally.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15] Even the updated European norms (prEN 12464-1 2019) that are supposed to address the higher lighting needs of the seniors do not take into consideration the possible different characteristics of people that have artificial IOLs implanted. 16,17 Implantation of a multifocal IOL completely modifies light transmission to the retina. Since the accommodation of the eye is iatrogenically disrupted, the uniform light distribution within the eye is also disrupted.…”
Section: Introductionmentioning
confidence: 99%
“…Some previous research also aimed to reveal the associations and correlations among different occupant behaviors [63][64][65][66][67][68], and the results showed that interactions exist between different behaviors, and these interactions can provide detailed recommendations for building energy conservation. Therefore, a systematic and comprehensive exploration of occupant behavior-related factors can better explain the components of energy consumption and achieve better energy-saving effects.…”
Section: The Impacts Of Occupant Behaviors On Building Energy Consumptionmentioning
confidence: 99%
“…The sky models developed, with luminance distributions determined for them in the zenith of the LVZ sky, reflect the state of the sky for individual degrees of cloudiness and diffusion of particles in the atmosphere. [18][19][20][21][22][23][24][25][26][27][28][29][30] According to the calculation procedure proposed by the CIE [17], geographical coordinates and time zone in the examined location are determined, and then the position of the Sun in the sky on a given day and at a specific time is determined. The declination angle , which determines the angular position of the blue equator relative to the ecliptic, is related to the next day in year n: 284 23, 45 sin 360 365…”
Section: Sky Luminance Calculationmentioning
confidence: 99%